2015
DOI: 10.4236/jtst.2015.13012
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Fabric Electrodes Used in ECG Signals Monitoring

Abstract: Wearable monitoring system is designed for skin stimulation of conductive adhesive, prolonged physiological monitoring and biocompatibility, whose core is fabric electrodes and it can feedback physiological status by analysis of abnormal electrocardiogram (ECG). Fabric electrode is a sensor to collect biological signals based on textile materials including signals acquisition, processing systems and information feedback platform and so on. In this paper, the design methods and classification of medical electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Even though metal threads provide good conductivity, which is very essential to be used as electrodes since they can easily detect the electrical activity of the heart over time, they still have limitations for use in wearable sensors. This is due to the fact that metal threads are heavier in weight compared to standard textile fibers, have limited flexibility affecting the fabric softness, are abrasive and unpleasant when in contact with the skin resulting in skin tingling, and cannot easily meet the requirement of being washable as some meal threads easily break during washing [ 84 , 85 ]. The metal must also be biocompatible, making most metals unsuitable.…”
Section: Textile-based Ecg Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though metal threads provide good conductivity, which is very essential to be used as electrodes since they can easily detect the electrical activity of the heart over time, they still have limitations for use in wearable sensors. This is due to the fact that metal threads are heavier in weight compared to standard textile fibers, have limited flexibility affecting the fabric softness, are abrasive and unpleasant when in contact with the skin resulting in skin tingling, and cannot easily meet the requirement of being washable as some meal threads easily break during washing [ 84 , 85 ]. The metal must also be biocompatible, making most metals unsuitable.…”
Section: Textile-based Ecg Electrodesmentioning
confidence: 99%
“…Metal-coated conductive textile materials are attractive for biopotential monitoring due to their high conductivity; however, they have certain limitations. Some metals are prone to corrosion, especially under conditions such as humidity, metals such as stainless steel have a high density which affects the fabric weight and softness, and metallic-coated fabrics have poor abrasion resistance [ 84 ]. Some examples of metal-coated textile-based ECG electrodes are shown in Figure 5 a–c, Figure 5 d presents a comparison of ECG signals collected using Ag/AgCl and silver-coated textile electrodes, and results revealed that major peaks are visible in both signals.…”
Section: Textile-based Ecg Electrodesmentioning
confidence: 99%
“…To design fabric electrodes it necessary to consider different aspects such as selection of materials, structure of fabric and conductive way of biological signal. It is very flexible electrodes with advantages of breathability, moisture permeability, soft and biological compatibility [9]. This type of sensors that can be used for recording bio-potential signals such as Electrocardiogram (ECG), Electromyography (EMG), and Electroencephalography (EEG) sensing.…”
Section: Introductionmentioning
confidence: 99%
“…In the article, the many methods that can be used to prepare fabric electrodes are reviewed, in order to get light fabric electrodes which have high conductivity and good conformability. As stressed in [64], "as a new generation of bio-signal acquisition material, fabric electrode has met the requirements of the development of modern medicine. Fabric electrode is different from traditional conductive materials in the characteristics of comfort, intelligence, convenience, accuracy and so on".…”
Section: Biosignal Monitoringmentioning
confidence: 99%
“…Also in [64], the design methods and classification of medical electrodes are discussed. In the article, the many methods that can be used to prepare fabric electrodes are reviewed, in order to get light fabric electrodes which have high conductivity and good conformability.…”
Section: Biosignal Monitoringmentioning
confidence: 99%